Kinerja Katalis Paduan ZnO dengan Tembaga dan Logam-Logam Golongan VIII pada Steam Reforming Etanol menjadi Hidrogen - Marwan Marwan (Jurnal Rekayasa Kimia & Lingkungan, 2009)
Steam reforming of ethanol to H2 using ZnO catalyst with promotor metal, i.e. copper or metal group VIII (Pd, Pt and Ni) has been investigated. Catalyst’s performances are tested further at micro reactor operating at atmosphere pressure. Ethanol solution 20% is injected to reactor at rate of 2 ml/jam and is mixed with nitrogen flow at 25 ml/menit. XRD analysis shows active phases existence of each promotor for produced catalyst. Reaction product includes H2, CO2, and a nonidentified component. Selectivity of H2 fromation depends on chosen promotor metal types, where the selectifity decreases as follows: Pt , Pd , Cu ≈ Ni. Reaction temperature and promotor concentration also influence selectifity H2. For catalyst 1% Pd/ZnO and 1% Pt/ZnO, selectivity H2 was optimum at temperature reaction 450oC. Whereas Pd promotor concentration’s increasing from 1% to 5% improves H2 selectivity.